INTERVAL OSCILLATION CRITERIA FOR HIGHER ORDER NEUTRAL NONLINEAR DIFFERENTIAL EQUATIONS WITH DEVIATING ARGUMENTS - Run Xu; Fanwei Meng (Journal of the Indonesian Mathematical Society, 2009)
"Pdf File"DOI : http://dx.doi.org/10.22342/jims.15.1.41.21-35